Urban air pollution and spatial strategic response - Chuyi Fang; Yuqing Zhao (Environmental Research Communications)
This study examines the spatial effects of urban air pollution in China, with a particular focus on how interregional competition shapes local environmental policies. We first develop a theoretical model in which environmental standards function as strategic complements, predicting that a prefecture’s pollution control efforts are positively influenced by those of neighboring regions. This hypothesis is then empirically tested using prefecture-level panel data from 2003 to 2019. The results reveal significant spatial spillovers in PM _2.5 concentrations across neighboring prefectures. Specifically, a 1 μg m ^−3 increase in neighboring air pollution is associated with up to a 0.89 μg m ^−3 rise locally, reflecting strong spatial dependencies in urban air quality. These findings underscore the necessity of cross-regional policy coordination to effectively mitigate air pollution in China’s rapidly urbanizing regions. These findings underscore the necessity of cross-regional policy coordination to effectively mitigate air pollution in China’s rapidly urbanizing regions.